2015
DOI: 10.1016/j.renene.2014.12.068
|View full text |Cite
|
Sign up to set email alerts
|

The use of alkaline earth oxides as pH modifiers for selective glycerol oxidation over supported Au catalysts

Abstract: Publication informationRenewable Energy, 78 : 89-92 Publisher ElsevierItem record/more information http://hdl.handle.net/10197/6287 Publisher's statement þÿ T h i s i s t h e a u t h o r s v e r s i o n o f a w o r k t h a t w a s a c c e p t e d f o r p u b l i c a t i o n i n R e n e w a b l eEnergy. Changes resulting from the publishing process, such as peer review, editing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was reported that the participation of these elements can lead to the generation of a new type of ensemble sites, including "Mn + -Aun," where Mn + = FeN + and Mn n+ , which are more efficient in CO activation than the parent Aum δ+ -Aun sites are. On the other hand, anionic Au was also recommended as an active site (Sullivan et al 2015). These species may be created if Au is deposited on a defect-rich support, for example, with an increased concentration of F-centers.…”
Section: Au/mgo Heterogeneous Catalystmentioning
confidence: 99%
“…It was reported that the participation of these elements can lead to the generation of a new type of ensemble sites, including "Mn + -Aun," where Mn + = FeN + and Mn n+ , which are more efficient in CO activation than the parent Aum δ+ -Aun sites are. On the other hand, anionic Au was also recommended as an active site (Sullivan et al 2015). These species may be created if Au is deposited on a defect-rich support, for example, with an increased concentration of F-centers.…”
Section: Au/mgo Heterogeneous Catalystmentioning
confidence: 99%
“…Most generated products are useful for fine chemicals synthesis, which are still being obtained by either expensive processes or by an enzymatic way [18]. Via this process, various catalysts can be applied such as Au based-catalysts [18][19][20][21][22], Pt based-catalyts [23][24][25] and Pd based-catalyst [26,27].…”
Section: Introductionmentioning
confidence: 99%